Community-Based Responsive Legal Transformation: A Legal Sociology Innovation to Eliminate Structural Poverty in Indonesia - Ibnu Imam Sumantri; Upik Mutiara; Rahmat Sihombing; Putri Regina Wijaya; Septra Risda Arking (CV. Publikasi Indonesia, 2026)
Poverty in Indonesia remains structural and enduring despite constitutional commitments to social justice. Viewing law as a social practice within a stratified society rather than merely a written standard, this article examines structural poverty from a sociological perspective. Based on a review of academic literature, relevant public policy studies, and laws and regulations, this research employs a juridical-sociological approach with qualitative methods. The results show that structural poverty in Indonesia is not only caused by financial constraints but is also created and perpetuated by the ways in which laws are written, implemented, and accessed. Law often operates administratively and procedurally rather than functioning fully as a tool for social transformation, owing to the gap between law in books and law in action, limited access to justice, and an elite-dominated legal culture. This article argues that, without institutional and cultural reforms, the inherent limitations of law within an unequal social system may actually exacerbate inequality rather than redress it. The distinctive conceptual contribution of this paper lies in reframing structural poverty as a failure of law to operate as a social practice, rather than merely a failure of economic or social policy. In addition to offering a critical perspective for developing community-based responsive legal reform aimed at substantive social justice in Indonesia, this study theoretically advances the sociology of law by establishing law as a constitutive component of the system that reproduces inequality.